1999
DOI: 10.1046/j.1365-3083.1999.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrastructural Study of Amyloid Intermediates in Aβ1–42 Fibrillogenesis

Abstract: Many attempts have been made to define early stages and intermediates in amyloid fibrillogenesis that may be susceptible to inhibition. We have developed an in vitro system, based on the use of A beta1-42 peptides, in which the development of prestages of protofilaments and protofilament and fibril formation could, for the first time, be followed by electron microscopy, supported by fluorescence spectrometry. The first recognizable ultrastructures after incubation of A beta1-42 peptides at 37 degrees C were gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 20 publications
7
35
1
Order By: Relevance
“…Thus, in an incubation of A␤(1-40) without CLC, aggregates collected at day 2 (within the ThT lag phase) are curvilinear, rough-edged protofibrils (Fig. 4a), as reported (1,2,7,(19)(20)(21). Aggregates collected from the same reaction at day 14 are typical amyloid fibrils (Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, in an incubation of A␤(1-40) without CLC, aggregates collected at day 2 (within the ThT lag phase) are curvilinear, rough-edged protofibrils (Fig. 4a), as reported (1,2,7,(19)(20)(21). Aggregates collected from the same reaction at day 14 are typical amyloid fibrils (Fig.…”
Section: Resultssupporting
confidence: 53%
“…CLC aggregates exhibit fine structure highly reminiscent of a particular type of protofibril often observed by EM (2,19,20) and atomic force microscopy (1,7,21). Normal A␤ protofibrils incubated in the absence of excess A␤ monomer tend to dissociate (7); whereas CLC stabilizes the A␤ aggregates, minimizing dissociation, these aggregates are incapable of elongating via monomer addition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When extracted from amyloid tissue the AA amyloid ®brils appeared to consist of, from SAP and HSPG detached, ®laments which after coiling assembled into parallel, twisting structures. Contrary to these ®ndings, we could not identify any stage that corresponded to these twisting structures when the in vitro ®brillogenesis of Ab 1±42 was monitored from the oligomeric state to the mature ®bril by EM [9]. Furthermore, when coincubated with Ab peptides the SAP molecules aligned on the surface of the mature ®brils.…”
Section: Discussioncontrasting
confidence: 76%
“…Amyloids are insoluble protein aggregates derived from the conversion of protofibrils into amyloid fibrils, which are formed by proteins characterized by a typical ␤-sheet structure. The commercially available human amyloid ␤ 42 (A␤ 42 ) is an amyloid-like peptide that can also form amyloid fibrils in vitro.…”
mentioning
confidence: 99%
“…Our data demonstrate that the monomer (D-Wt-M) forms oligomers that adopt an amyloid-like structure. The Pmp21-D oligomers (collectively referred to as D-Wt-O) are comparable in size and shape to protofibrils of A␤ 42 . Comparison of the oligomerization capacity of D-Wt with that of a previously analyzed mutant form (D-Mt) with poor adhesion properties revealed that the FXXN motif in D-Wt contributes significantly to the formation of oligomers.…”
mentioning
confidence: 99%